2008
DOI: 10.1021/jp8039803
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Hydration and Diffusion of Protons in Perfluorosulfonic Acid Membranes with Molecular Dynamics Simulations

Abstract: Classical molecular dynamics (MD) simulations were performed to determine the hydrated morphology and hydronium ion diffusion coefficients in two different perfluorosulfonic acid (PFSA) membranes as functions of water content. The structural and transport properties of 1143 equivalent weight (EW) Nafion, with its relatively long perfluoroether side chains, are compared to the short-side-chain (SSC) PFSA ionomer at an EW of 977. The separation of the side chains was kept uniform in both ionomers consisting of -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
143
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(163 citation statements)
references
References 111 publications
15
143
4
Order By: Relevance
“…Since we have attempted to limit the entanglement of the polymer chains when generating the systems, and since the least entangled systems by Knox and Voth also seem to be the ones closest to experiment, one might speculate that this is one key feature leading to the observed features in the scattering experiments, as expressed in the so-called ionomer peak. In contrast to some earlier work [54,69], we do not observe significant differences between Nafion and Hyflon. Since both the 'cylindrical' model and the 'random' model proposed here as well as most of Voth's model systems reproduce the experimental scattering data satisfactorily, we must conclude that the scattering data alone are not sufficient to elucidate the structure of systems as complex as proton exchange membranes in water, hence the ongoing debate over their morphology.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Since we have attempted to limit the entanglement of the polymer chains when generating the systems, and since the least entangled systems by Knox and Voth also seem to be the ones closest to experiment, one might speculate that this is one key feature leading to the observed features in the scattering experiments, as expressed in the so-called ionomer peak. In contrast to some earlier work [54,69], we do not observe significant differences between Nafion and Hyflon. Since both the 'cylindrical' model and the 'random' model proposed here as well as most of Voth's model systems reproduce the experimental scattering data satisfactorily, we must conclude that the scattering data alone are not sufficient to elucidate the structure of systems as complex as proton exchange membranes in water, hence the ongoing debate over their morphology.…”
Section: Discussioncontrasting
confidence: 99%
“…4). This is at variance with the work of Cui et al [68,69] who observed a less dispersed water distribution in Nafion as compared to Hyflon.…”
Section: Cluster Analysiscontrasting
confidence: 83%
“…The classical molecule dynamics (MD) and ab initio molecular dynamics (AIMD) methods were used to determine proton mobility as a function of hydration conditions and sulfonated function rings [14][15]. Studies on SSC PFSA membrane fragments show that the formation of hydrogen bonds between water molecules is highly dependent on acid ring connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Among these membranes, Nafion is studied extensively by experiments [2,6] and computational methods. [7][8][9][10][11][12] However, the conductivity of Nafion membrane is strongly dependent on its hydration. [13][14][15][16][17] The operating temperature of fuel cells using Nafion is limited to the boiling point of water, that is, 100 C, and at this temperature, there is low tolerance of the electro-catalyst like platinum against CO poisoning.…”
Section: Introductionmentioning
confidence: 99%